2023
DOI: 10.1002/aoc.7338
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the antimicrobial, antioxidant and cytotoxic activities of organyltellurium (IV) complexes incorporating 2‐hydroxy‐1‐naphthaldehyde schiff base ligand: Synthesis, spectroscopic investigations and theoretical studies

Mahak Dalal,
Jai Devi,
Nidhi Antil
et al.

Abstract: In this study, Schiff base ligand 1,1′‐((propane‐1,3‐diylbis [azaneylylidene]) bis (methaneylylidene))bis (naphthalen‐2‐ol) based Organyltellurium (IV) complexes were synthesized with formulae C32H27ClN2O3Te (5a)\C31H25ClN2O3Te (5b)\C32H27ClN2O3Te (5c)\ C39H34N2O4Te (5d)\ C37H30N2O4Te (5e)\ C39H34N2O4Te (5f) for acquiring a potential therapeutic agent. The synthesized compounds were characterized by ultraviolet–visible (UV–Vis), FT‐IR, 1H‐NMR, 13C‐NMR, mass spectrometry, molar conductance, elemental analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…In the context of anti-TB analysis, complex (10) demonstrated a higher level of effectiveness (MIC value 0.006 ± 0.001 μmol/mL) that was nearly double than the streptomycin, meanwhile, complexes (6) and ( 9) exhibit comparable TB inhibition ability to streptomycin. The examination of anti-inflammatory properties of compounds (1-10) showed that again complex (10) has the lowest and comparable IC 50 value (6.75 ± 0.09 μM) to diclofenac sodium which signifies its superior efficacy in managing inflammation deformities, whereas (5), ( 6), (8), and (9) exhibit significant inflammation inhibition efficacy. In the antibacterial and antifungal investigations, again complex (10) (0.0066 μmol/mL) has a comparable MIC value to standard drugs against S. aureus, B. subtilis, E. coli, P. aeruginosa, and R. oryzae, whereas it was proved to be more efficient (0.0066 μmol/mL) in controlling C. albicans deformities in comparison of fluconazole.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of anti-TB analysis, complex (10) demonstrated a higher level of effectiveness (MIC value 0.006 ± 0.001 μmol/mL) that was nearly double than the streptomycin, meanwhile, complexes (6) and ( 9) exhibit comparable TB inhibition ability to streptomycin. The examination of anti-inflammatory properties of compounds (1-10) showed that again complex (10) has the lowest and comparable IC 50 value (6.75 ± 0.09 μM) to diclofenac sodium which signifies its superior efficacy in managing inflammation deformities, whereas (5), ( 6), (8), and (9) exhibit significant inflammation inhibition efficacy. In the antibacterial and antifungal investigations, again complex (10) (0.0066 μmol/mL) has a comparable MIC value to standard drugs against S. aureus, B. subtilis, E. coli, P. aeruginosa, and R. oryzae, whereas it was proved to be more efficient (0.0066 μmol/mL) in controlling C. albicans deformities in comparison of fluconazole.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a 30 mL methanolic solution of thiosemicarbazone ligands HL 1 (1) or HL 2 (2) was stirred for 3-4 h with cobalt (II), nickel (II), copper (II), zinc (II) acetates in a 2:1 M ratio to form complexes (3)(4)(5)(6)(7)(8)(9)(10). The obtained different colored solid compounds were washed with methanol and further purified through recrystallization in THF (Scheme 1).…”
Section: Synthetic Protocol Of the Compounds (1-10)mentioning
confidence: 99%
See 3 more Smart Citations